Classification, Diagnosis, and Prognosis of Cardiomyopathy: A Comprehensive Narrative Review - Yubin Jin; Wenjing Che; Jiuyue Yang; Shumin Chang; Wenqi Bao; Xinyue Ren; Pengyu Yu; Aijie Hou (Reviews in Cardiovascular Medicine)
Cardiomyopathy denotes a group of heart diseases caused by structural or functional heart muscle disorders, with various genetic and non-genetic etiologies. Based on the current literature, this narrative review synthesizes key findings from available information on the classification, diagnosis, and prognosis of inherited or acquired cardiomyopathies. Following a different approach to prior systematic reviews, this study does not implement any formal inclusion or exclusion criteria or structured search strategy. However, this review does consider the evidence of influential studies, prominent cardiology guidelines, and expert consensuses to provide a comprehensive overview of recent advancements in the field. Further, explication is performed for the latest advances in genetic mutations, diagnostic imaging techniques, and therapeutic techniques. All diagnoses involve clinical presentations, imaging, and laboratory tests. Future research directions include personalized therapy, quantitative imaging techniques, and new drug treatments. This review highlights cardiomyopathy research by emphasizing the integration of precision medicine, advanced imaging, and molecular diagnostics. Future research on cardiomyopathy should include precision medicine and personalized therapies with an exhaustive integration of techniques and resources to catalyze further innovations in diagnostics and therapeutic approaches. Thus, this narrative review will provide clinicians and researchers with insight into the future of cardiomyopathy management by summarizing key developments and trends.